Gastronomic tourism of Sebuyau, Malaysia: an ecosystem for sustainable development / Abang Zainoren Abang Abdurahman... [et al.] - Abang Abdurahman, Abang Zainoren; Ahmad, Johanna Adlin; Ali, Jati Kasuma; Bujang Khedif, Lenny Yusrina; Bohari, Zubaidah; Kibat, Silverina Anabelle (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Sebuyau is a fishing village located an-hour drive from Kuching town of Sarawak, Malaysia. As a fishing village, Sebuyau is rich in seafood resources and local culinary experience that can be a stepping stone for gastronomic tourism. However, the local Sebuyau stakeholders has yet to leverage on this opportunity as there is a lack of promotion of the town for its culinary experiences. As such, the premise of the paper is based on two objectives which are to identify the community's local gastronomy, and to propose the gastronomic tourism ecosystem based on the feedback given by the local community. The methodology employed is qualitative approach by conducting personal interviews with the local food service operators, contestants and local resident attending a community cooking competition in Sebuyau. During the competition, the culinary menus generated from the events were recorded to determine the cuisine of Sebuyau. The findings identified 54 types of localized cuisines. The challenges identified in developing gastronomic tourism in Sebuyau include the lack of knowledge among the local community on starting a business including financial management, loans and licencing application, and knowledge on food handling. In conclusion, six components have been identified as the ecosystem for Sebuyau's stakeholders which include training, financial and assistance advisory, infrastructure development, license and permit, innovation programs, and leadership. These ecosystems can serve as guidelines for stakeholders in planning for development of Sebuyau's gastronomic tourism and contribution towards Sustainable Development Goals (SDGs) 8 and 9.